EVALUATION OF ENERGY EFFICIENCY OF THE NITROGEN-DOPED Co3O4 (100) SURFACE FOR WATER DISSOCIATION - G.A. Kaptagay; N.O. Koilyk; A.M. Tatenov; N.A. Sandibaeva; A.A. Dutbayeva (Academic Scientific Journal of Computer Science, 2019)
Co3O4 is easily available and thermodynamic stable oxide in a wide interval of temperatures and conditions with rich concentration of oxygen. Also Co3O4 among oxides of transition metals – useful materials for gas sensors, storage systems of energy and materials of anodes of lithium - ion batteries, zink-air batteriesand other energy applications. For enhancing energy efficiency of decomposition of water molecules on cobalt oxide surfaces was studied effect of various dopants. One of the promising doping materials for Co3O4 is nitrogen. In paper we report the results of theoretical investigations of water adsorption on undoped and nitrogen-doped Co3O4 (100) surface by means of the plane-wave periodic density functional theory (DFT) calculations combined with the Hubbard-U approach and statistical thermodynamics. We discuss the effect of nitrogen-doping of the Co3O4 (100) surface and calculated oxygen evolution reaction overpotential based on the Gibbs free-energy diagram of undoped and N-doped surfaces. Results of calculations of the overpotentials of water molecule decomposition on the nitrogen-doped (100) surface of cobaltum oxide demonstrate generally the decreased values in comparison withundoped surface with some deviation on considered steps of decomposition.